A revision of the rare flower beetle genus Macronotops Krikken (Coleoptera: Scarabaeidae: Cetoniinae) from Asia with biological notes - Qiu, Jian-Yue; Xu, Hao; Chen, Li (Zootaxa, 2019)
Based on examination of all available types and a large number of additional specimens, the poorly studied genus Macronotops Krikken, 1977 is revised. Thirteen species are recognized, including four new species herein described, M. biserratus Qiu, Xu & Chen, new species from Laos, M. dianensis Qiu, Xu & Chen, new species from China (Yunnan) and Vietnam, M. miksici Qiu, Xu & Chen, new species from China (Yunnan), Myanmar, and India, and M. medogensis Qiu, Xu & Chen, new species from China (Xizang). The neotype of Macronota fulvoguttata Fairmaire, 1891 is designated. Macronotops fulvopilosus (Fairmaire, 1894) is considered as an independent species, and M. olivaceofuscus (Bourgoin, 1916) revised status, formerly regarded as subspecies of M. vuilleti (Bourgoin, 1916), is elevated to species rank. Pleuronota subsexmaculata Ma, 1992, new synonym and P. hefengensis Ma, 1992, new synonym are placed as junior synonym of M. olivaceofuscus and M. fulvoguttatus, respectively. All previous records of M. sexmaculatus (Kraatz, 1894) in southern China are verified as misidentification of M. olivaceofuscus; M. sexmaculatus is recorded from China (Xizang) for the first time, and its distribution appears to be limited to the southern side of the eastern Himalayas. Macronotops olivaceofuscus and M. vuilleti are newly recorded from Vietnam and China, respectively. Sima of Myanmar, the type locality of M. ovaliceps (Arrow, 1941), is located at the border of Myanmar and China (Yunnan); and more specimens of this species were obtained from western Yunnan. Habitus and diagnostic characters are illustrated for all species. Key to species and notes on natural history of this genus are also provided.